Vibration acoustics characterization of bearing system based on bearing acoustic vibration coupling algorithm - Yue, Xiali (Engineering Research Express, 2025)
To study the vibration and acoustic characteristics of bearing systems under the influence of inner and outer ring waviness, a bearing acoustic vibration coupling algorithm based on Hertz contact theory was developed. The core of this algorithm lies in establishing a nonlinear contact force model for bearings based on Hertz contact theory, and combining it with a six degree of freedom mechanical model to simulate the dynamic behavior of bearings; By combining transient dynamics analysis with boundary element method, accurate calculation of bearing vibration response and radiated sound field has been achieved. The research results indicate that the maximum amplitude of the inner and outer ring waviness has a significant impact on the vibration and peak sound pressure of the bearing seat, and the multiple relationship between wave number and ball number also plays an important role in the vibration response and sound pressure. Compared with existing methods, the innovation of this algorithm lies in its comprehensive consideration of the nonlinear contact characteristics and vibration acoustic coupling mechanism of bearings, achieving a more comprehensive characterization of the dynamic behavior of bearings; Its effectiveness has been verified, and the prediction accuracy of vibration and peak sound pressure has been significantly improved, with prediction errors reduced by about 24% and 25%, respectively. This algorithm provides a new perspective and more effective analysis tool for fault diagnosis, noise control, and performance evaluation of bearings, which helps to improve the operational efficiency and reliability of mechanical equipment.